Ekspresi dan Purifikasi Protein Rekombinan Non-Struktural NS1 Virus Dengue Serotipe 1 Strain Indonesia Pada Pichia Pastoris - Lestari, Chirstina Whinie; Narita, Vany; Soediro, Tjahjani Mirawati; Sjarurachman, Agus (Jurnal Biotek Medisiana Indonesia, 2016)
Dengue infection remains a public health problem in Indonesia. In the framework of the independence of the national product, pursued research and development of raw materials that can be used for diagnostic kit and vaccine candidates. The objective of this study was to express and purify recombinant proteins non-structural NS1 dengue virus serotype 1 (DENV-1) of Indonesia strain (915 846) in Pichia pastoris expression system with âhalalâ system that can be used for the development of diagnostic kits and vaccines. The dengue virus serotype 1 strain Indonesia (915846) was used to construct the NS1 DENV-1 gene by PCR. Then NS1 DENV-1 gene cloned into the vector pPICZÎ±B and transformed into Pichia pastoris yeast cells, then verified with sequencing. Recombinant protein NS1 DENV-1 was secreted expression in P. pastoris. Characterization of antigenicity was did by ELISA, Western Blot and purified by the method of metal-chelating affinity chromatographic (MCAC) column. The recombinant protein with a size of 45 kDa secreted into the supernatant of P. pastoris with methanol induction and purified. The recombinant protein can bind to monoclonal antibodies and serum of patients infected with dengue virus serotype 1. These results indicate that the recombinant protein NS1 DENV-1 strain Indonesia (915 846) can be produced efficiently in P. pastoris secreted expression system is halal and still functional as an antigen that can be used for the development of diagnostic kits and vaccines.